(untitled) (Development Engineering Conferences Center Articles Database, 2026)
The convergence of advanced technological domains—namely precision aquaculture, molecular diagnostics, remote sensing, and digital health surveillance—has catalysed a paradigm shift in both fisheries science and veterinary medicine. This review synthesises the state-of-the-art of integrated technologies including next-generation sequencing (NGS), CRISPR-based diagnostics, the Internet of Things (IoT), blockchain for traceability, and machine learning for disease modelling. Special emphasis is placed on cross-sectoral applications where veterinary diagnostic platforms enhance aquatic animal health management, and fisheries monitoring tools inform terrestrial livestock epidemiology. The paper evaluates the efficacy of real-time biosensing, vaccine delivery systems, and environmental DNA (eDNA) analytics as dual-use technologies. Furthermore, it addresses regulatory harmonisation and One Health implications of merging these disciplines. By critically analysing case studies from both sectors—such as the use of portable NGS on fishing vessels and mobile veterinary clinics, CRISPR assays for both African swine fever and white spot syndrome virus, and satellite remote sensing for Rift Valley fever and harmful algal blooms—this review provides a roadmap for interoperable technological frameworks that improve biosecurity, reduce antimicrobial resistance, and optimise production sustainability. The findings underscore that only through deliberate integration of engineering, data science, and veterinary medicine can the global challenges of aquatic and terrestrial food systems be met effectively.